Effects of drinking water distribution system on Vibrio amounts in biofilm - SHI Ya; SHI Xiaofeng; ZHANG Yongjing; LIU Jingqing; CHENG Dongqing (浙江大学学报. 农业与生命科学版, 2016)
With the development of modern industries, drinking water in residential area and public building were supplied by water distribution systems. The drinking water distribution system is the final step from water plants to the users, and therefore is essential to assure drinking water safety for customers. Previous studies confirmed that many bacteria in the drinking water distribution systems existed as biofilm, which could induce corrosion and scaling of the pipe walls, reduce the water quality and water-carrying capacity of the pipelines. Moreover, as the pathogens growing in the biofilms transferred in the pipelines, the risks caused by these microorganisms would increase. Vibrio species is an estuarine bacterium widely distributed in the natural aquatic environment around the world. Among the discovered 76 kinds of Vibrio species, at least 12 kinds have pathogenic effect on human, and often result in severe diarrhea and dehydration. We found the Vibrio species in our previous survey of pathogenic bacteria in biofilm, indicating that the residents were at potential risk from Vibrio species. Therefore, the effect of pipe materials, pipe ages, and pipe diameters on amount of Vibrio species in biofilm of drinking water distribution system was necessary to investigate.In this study, 12 biofilm samples were collected from the drinking water distribution system in east China. Vibrio was isolated using thiosulfate-citrate-bile salts-sucrose (TCBS) agar medium and was identified according to their biochemical reaction characteristics using biochemical identification kit for Vibrionaceae GYZ-9V. The amounts of total bacteria were determined by a spread-plating method according to the Ministry of Health Standard Examination Methods for Drinking Water (2006). Samples and their dilutions were spread on Petri dishes with nutrient agar medium. Analysis of variance (ANOVA) by a least significant difference test was used to compare Vibrio counts from different pipe materials, ages and diameters.The results showed that Vibrio species could be detected in nodular cast iron, galvanized steel and stainless steel clad pipes, but not in plastic pipe. The Vibrio species amount on the biofilm attached to the nodular cast iron pipe (212±39.40 CFU/cm2) was significantly higher than those attached to the galvanized steel pipe (4.85±1.03 CFU/cm2) and stainless steel clad pipe (0.66±0.21 CFU/cm2). However, the rank of total bacteria amount was galvanized steel pipe > nodular cast iron pipe≈plastic pipe > stainless steel clad pipe. Pipe age had little influence on Vibrio amounts from galvanized steel and nodular cast iron pipes. Nodular cast iron pipe with a nominal diameter of 200 mm had the highest amount of Vibrio species (2.65×103±204 CFU/cm2), followed by 150 mm (212±39.40 CFU/cm2) and 300 mm (44.20±6.88 CFU/cm2), and the tendency of total bacteria amount was similar with Vibrio species.In conclusion, contamination from Vibrio species with varying levels is observed in nodular cast iron, galvanized steel and stainless steel clad pipes, but not in plastic pipe. The different pipe materials, especially nodular cart iron pipe, have strong influence on Vibrio species amount in biofilm from drinking water distribution system; therefore, the potential risks of Vibrio species from nodular cast iron pipe should be taken into consideration while laying the pipelines.